Membrane Pump Operation Synchronicity (Criticality) in Epidermal Cells: The Possibility of Quantifying the Level of Synchronization - V.I.Petukhov; Е.V.Dmitriev; L.Kh.Baumane; A.V.Skalny; Yu.N.Lobanova; A.R.Grabeklis (International Journal of Negative Results, 2018)
The authors analyze the results of atomic emission spectrometry of hair samples for Al, Cd, Fe, Cr, Cu, Li, Pb, V, and Zn in 952 healthy subjects and 952 liquidators of the Chernobyl nuclear power plant accident. Using correlation analysis (Pearson) of the obtained data, the authors have found pair correlations between metal concentration values. According to the authors, criticality or synchronization (as a particular case of the critical state of the system) can be inherent in all ATP-dependent membrane pumps (P-type) controlling metal-ligand homeostasis in epidermal cells. A quantitative criterion (synchronization index) is proposed to measure the level of criticality (synchronization) in the functioning of membrane ATPases.
Keywords: nitric oxide